Prognosis, Communication, and Advance Care Planning in Heart Failure: A Module for Students, Residents, Fellows, and Practicing Clinicians - April Zehm; Charlotta Lindvall; Kimberly Parks; Kristen Schaefer; Eva Chittenden (Association of American Medical Colleges, 2017)
Introduction The increasing prevalence, high symptom burden, and medical advances that often prolong the advanced phase of heart failure mandate an organized and thoughtful approach to medical decision making. However, many clinicians have difficulty discussing prognosis and goals of care with patients. Barriers include disease- and therapy-specific prognostication challenges in heart failure and a lack of evidence-based primary palliative care education initiatives. Methods In response, we developed this 45-minute training module, which consists of a case-based small-group session and a communication guide. The curriculum highlights prognostication challenges in heart failure and introduces an illness trajectory-based framework to cue iterative goals of care conversations. Results We piloted this learning module with 46 internal medicine residents and interdisciplinary palliative care fellows in groups of three to 15 and obtained anonymous quantitative and qualitative postsession learner survey data to examine feasibility and acceptability. Trainees rated the session highly. One hundred percent of learners either strongly agreed or agreed the session was clinically useful. Learners unanimously found the teaching methods effective, and most felt they could easily apply these skills to their clinical work. In open-ended feedback, learners said the session gave them a better understanding of the heart failure illness trajectory, an improved framework for discussing goals of care with heart failure patients, and specific language to use when having these discussions. Discussion This module represents a new paradigm for teaching both prognostication and advance care planning in heart failure in which illness trajectory guides timing and content of goals of care conversations.